Pengembangan Kawasan Minapolitan Sebagai Alternatif Ekowisata untuk Meningkatkan Perekonomian Desa Lango Kecamatan Pante Ceureumen - Taufiq, Taufiq; Ariska, Nana; Amarullah, Amarullah (Pencerah, 2025)
Lango Village, located in Pante Ceureumen Subdistrict, West Aceh Regency, possesses significant natural resource potential, yet its utilization remains suboptimal. To enhance economic productivity and environmental sustainability, the minapolitan concept is implemented—an integrated system of agriculture and aquaculture that utilizes organic waste as fertilizer and recirculated water as a habitat for fish cultivation. This study aims to develop a minapolitan area through a participatory approach and community empowerment. The research methodology comprises several stages: initial data collection, feasibility study, design, community training, implementation, and evaluation. The development plan includes infrastructure construction, technical training, marketing strategies, and continuous monitoring and evaluation. Potential risks such as community resistance, infrastructure damage, weather dependence, and limited capital are addressed through mitigation strategies involving socialization, maintenance planning, climate adaptation, and funding resource identification. The results indicate that the local community has improved income levels, optimized the use of local resources, and established a sustainable economic system in Lango Village. The successful implementation of the minapolitan model positions Lango Village as a potential benchmark for efficient and sustainable resource management in surrounding regions.